2017
DOI: 10.1509/jm.15.0402
|View full text |Cite
|
Sign up to set email alerts
|

The Sting of Social: How Emphasizing Social Consequences in Warning Messages Influences Perceptions of Risk

Abstract: This research examines the effects of warning messages that emphasize the social consequences of negative health outcomes. The authors demonstrate that highlighting social (vs. health) consequences leads to greater perceived temporal proximity of and increased perceived vulnerability to the outcome, thereby affecting risk perceptions, behavioral intentions, and customer perceptions of actual experience. They document this effect across five studies in different health domains including flossing (Study 1), soda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 57 publications
(100 reference statements)
4
50
1
Order By: Relevance
“…Therefore, it is important to connect their general knowledge of NCDs with their specific risky behaviour. We chose simple messages to warn a risky behaviour such as over-intake of sugar as the first step 25 , 26 , because the concept of total dietary energy intake would be difficult to comprehend for most people, who frequently misreport their energy intake. 27 , 28 Once the level of knowledge is improved, the message should be elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to connect their general knowledge of NCDs with their specific risky behaviour. We chose simple messages to warn a risky behaviour such as over-intake of sugar as the first step 25 , 26 , because the concept of total dietary energy intake would be difficult to comprehend for most people, who frequently misreport their energy intake. 27 , 28 Once the level of knowledge is improved, the message should be elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the findings of Purmedi et al (2017) research that the location of the warning label placement affects the effectiveness of the warning label. After conducting a literature study and processing the previous research data, many assumptions and expectations need to be confirmed through the research that we have put in the research model as follows: As explained in the previous section, research on the label warning in social marketing has proven that the warning label can influence the intention to purchase a product (Kees et al, 2006;Halim, 2015;Effertz 2013;Morvan, 2011;Rajagopal 2017). In line with the development of research on warning labels, the analysis of this topic has become increasingly sharp, as in Murdock and Rajagopal (2017), Kees et al (2006), Halim (2015).…”
Section: Conceptual Model Overviewmentioning
confidence: 99%
“…After conducting a literature study and processing the previous research data, many assumptions and expectations need to be confirmed through the research that we have put in the research model as follows: As explained in the previous section, research on the label warning in social marketing has proven that the warning label can influence the intention to purchase a product (Kees et al, 2006;Halim, 2015;Effertz 2013;Morvan, 2011;Rajagopal 2017). In line with the development of research on warning labels, the analysis of this topic has become increasingly sharp, as in Murdock and Rajagopal (2017), Kees et al (2006), Halim (2015). Although many previous studies have shown that the effectiveness of warning labels influences consumer consumption patterns, social marketing scholars still worry that the promotion of health-threatening products such as beverages and junk foods is increasingly taking a greater role in creating unwanted consumption behaviors.…”
Section: Conceptual Model Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Through this article, Mitchel Murdock and Priyali Rajagopal (2017) contribute to this literature by proposing joint warning messages that couple severe, long-term health consequences with more immediate social consequences. They test the efficacy of this approach across five studies.…”
Section: The Sting Of Social: How Emphasizing Social Consequences In mentioning
confidence: 99%